2022
DOI: 10.3389/fcvm.2022.868675
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Function Assessment in Fetuses With Ductus Arteriosus Constriction: A Two-Dimensional Echocardiography and FetalHQ Study

Abstract: BackgroundFetal ductal constriction (DC) is associated with excessive polyphenol-rich food (PRF) consumption during pregnancy. However, the effect of this hemodynamic change on fetal cardiac function still needs to be elucidated. Therefore, this study aimed to evaluate the cardiac function of fetuses with PRF-related DC and to describe serial observations of cardiac function changes.MethodsWe compared the traditional echocardiographic indices, including morphological, hemodynamic, and functional parameters, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Recent studies confirmed that fetal hearts with DA constriction show significant ventricular remodeling and biventricular dysfunction through conventional ultrasound parameters [31,32].…”
Section: Fetal Ductus Arteriosus Pathologymentioning
confidence: 81%
“…Recent studies confirmed that fetal hearts with DA constriction show significant ventricular remodeling and biventricular dysfunction through conventional ultrasound parameters [31,32].…”
Section: Fetal Ductus Arteriosus Pathologymentioning
confidence: 81%